On the Optimal Reconfiguration of Radial AC Distribution Networks Using an MINLP Formulation: A GAMS-Based Approach (2022)
This paper addresses the problem of the optimal reconfiguration of medium-voltage distribution networks by proposing a mixedinteger nonlinear programming (MINLP) model. The objective function of this optimization model is the minimization of the total power losses in all the branches of the network, considering active and reactive power balance equations, voltage regulation bounds, and device capabilities, among others. The proposed MINLP formulation works with branch-to-node incidence that allows representing the active and reactive power flow in branches as a function of the real and imaginary components of the voltages and currents. The solution of the MINLP model is reached through the general algebraic modeling system widely known as the GAMS package while presenting it in the form of a tutorial. This software allows implementing the proposed model a in compact way, which is solved via branch and bound methods. Two test feeders comprising 5 and 14 nodes allow demonstrating the fidelity of the proposed MINLP model regarding power loss minimization when compared to that reported in the specialized literature. © 2022, Universidad Nacional de Colombia. All rights reserved.